THEMATIC MAPPING OF RESEARCH ON CHILD MARRIAGE: A REVIEW OF GLOBAL TRENDS AND DIRECTIONS IN SCIENTIFIC LITERATURE - Abshenova L.U. (European Research Materials, 2025)
This article presents a comprehensive bibliographic and thematic analysis of scientific publications on child and early marriage among girls. Drawing on data from the Scopus database, the study maps the evolution of academic interest, key research clusters, and geographic patterns in global literature over the past two decades. The analysis identifies six major thematic clusters centered on legal regulation, reproductive health, gender-based violence, education, humanitarian crises, and cultural practices. The findings reveal the high interdisciplinarity of the topic, involving contributions from gender studies, demography, sociology, public health, anthropology, and law. Particular attention is paid to the underrepresentation of Central Asia, Latin America, and Eastern Europe in existing research, highlighting important regional gaps. The study also shows how academic discourse reflects broader policy and advocacy efforts aligned with the Sustainable Development Goals, especially those related to gender equality, health, and education. By providing a structured overview of the scientific landscape, this study contributes to a better understanding of current knowledge, identifies blind spots, and suggests directions for future interdisciplinary and transnational research on child marriage